2010
DOI: 10.2478/s11658-010-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

ZNF300, a recently identified human transcription factor, activates the human IL-2Rβ promoter through the overlapping ZNF300/EGR1 binding site

Abstract: ZNF300 was recently identified as a member of the human KRAB/C2H2 zinc finger protein family. Little is known about the role of ZNF300 in human gene regulation networks. In this study, the DNA-binding property of ZNF300 was further analyzed. We found that the recombinant ZNF300 could bind to the binding site 5′-GCGGGGGCG-3′ of Egr1, another member of the KRAB/C2H2 zinc finger protein family. Similarly, recombinant Egr1 also showed a similar binding affinity to the ZNF300 binding site 5′-CTGGGGGCG-3′. Bioinform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…3 Functions of significantly differentially expressed genes in placenta. Venn diagrams of function categories for DEGs with known gene ontologies [ 39 , 84 , 85 , 93 , 97 , 98 , 100 106 , 114 126 ]. Autosome genes are underlined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Functions of significantly differentially expressed genes in placenta. Venn diagrams of function categories for DEGs with known gene ontologies [ 39 , 84 , 85 , 93 , 97 , 98 , 100 106 , 114 126 ]. Autosome genes are underlined.…”
Section: Resultsmentioning
confidence: 99%
“…Differentially expressed transcription factors in first trimester may explain sex differences in later pregnancy complications. For example, ZNF300 (1.58-fold upregulated in females) encodes a transcription factor protein that shares DNA binding sites with Early growth response 1 (Egr1), a zinc finger transcription factor that is elevated in placentas of pregnancies that later develop preeclampsia, which is more common in pregnancies with a male fetus [ 15 , 106 , 107 ]. Increased expression of ZNF300 in females may function as a competitor of EGR1 binding sites, leading to reduced rates of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…We next explored how ZNF300 regulate the NF‐κB pathway. Our previous study had indicated the presence of putative ZNF300 binding sites (C(t/a)GGGGG(g/c)G) in the promoter regions of genes such as IL2RB , CD44 and TRAF2 [17, 18]. Here, we focused on the putative ZNF300 binding site in the proximity of the promoter of the gene‐encoding TRAF2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…binding sites (C(t/a)GGGGG(g/c)G) in the promoter regions of genes such as IL2RB, CD44 and TRAF2 [17,18]. Here, we focused on the putative ZNF300 binding site in the proximity of the promoter of the gene-encoding TRAF2 (Fig.…”
Section: Znf300 Regulates Transcription Of Traf2mentioning
confidence: 99%
“… 74 , 75 Another blood-specific eQTL includes ZNF300, which is downregulated by Crohn risk allele and is involved in activating the IL2βR expressed highly on T-regulatory cells. 76 Other identified eQTLs were involved in T-cell skewing. For example, FOSL2 is an AP1 transcription factor, which is a putative regulator of plasticity and repressor of TH17 cells.…”
Section: Discussionmentioning
confidence: 99%